Fast Gain Switching on TwinRX USRPs - Engelhardt, Maximilian; Beuster, Julia; Andrich, Carsten; Ihlow, Alexander; Del Galdo, Giovanni (2022 16th European Conference on Antennas and Propagation, EuCAP 2022, 2022)
In this paper, we investigate the gain switching performance of the software-defined radio (SDR) universal software radio peripheral (USRP) X310 with the TwinRX daughterboard and propose a method to optimize it for fast transitions. This receiver uses a complex structure of two switchable amplifiers and two digital step attenuators to realize the wide gain setting range of up to 92 dB. Our measurements of the settling time show that the bulk of transitions between two gain settings take below 1.5 mumathrms, but some require more than 50 μs, caused by the power-up of the switchable amplifiers. Based on this knowledge, we propose a modified switching regime, in which the amplifiers are not toggled in time-critical phases, e.g., during a running measurement, so that a transition time of 1.5 mumathrms can be reliably realized. Thus, a gain switching range of 62 dB is achieved, within which, for example, a fast automatic gain control can be realized.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Software-defined radio; TwinRX; USRP